2015
DOI: 10.1016/j.bbmt.2014.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Expansion and Homing of Umbilical Cord Blood Hematopoietic Stem and Progenitor Cells for Clinical Transplantation

Abstract: The successful expansion of hematopoietic stem and progenitor cells (HSPCs) from umbilical cord blood (UCB) for transplantation could revolutionize clinical practice by improving transplantation-related outcomes and making available UCB units that have suboptimal cell doses for transplantation. New cytokine combinations appear able to promote HSPC growth with minimal differentiation into mature precursors and new agents, such as insulin-like growth factor-binding protein 2, are being used in clinical trials. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 113 publications
2
34
0
Order By: Relevance
“…To further assess the quality and variation of the UCB samples, we also examined the expression of CD34, a HSC marker. In the current study, the percentage of CD34-positive cells in the UCB MNCs was fairly low (range, 0 to 20%; median, 2.2%), but in the range previously reported for HSCs from peripheral blood and BM [35, 36]. …”
Section: Discussionsupporting
confidence: 49%
“…To further assess the quality and variation of the UCB samples, we also examined the expression of CD34, a HSC marker. In the current study, the percentage of CD34-positive cells in the UCB MNCs was fairly low (range, 0 to 20%; median, 2.2%), but in the range previously reported for HSCs from peripheral blood and BM [35, 36]. …”
Section: Discussionsupporting
confidence: 49%
“…5 Current studies to enhance clinical UCB transplantation outcomes have focused on expanding UCB HSPC ex vivo and/or improving their BM homing. 2,3,6 Erythropoietin (EPO) affects the fate of hematopoietic progenitor cells (HPCs) in favor of erythroid differentiation. 7 In addition, circulating HPCs rapidly decline after birth, 8,9 which has been shown to coincide with a decrease in EPO blood concentration.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, other studies have demonstrated that the co-infusion of MSCs at the time of UCB transplantation has no effect on the kinetics of engraftment and on the prevention of GvHD [52], inhibits thymic reconstitution, and has a negative effect on patient’s survival [53]. MSCs have been also employed to stimulate ex vivo UCB-derived HSC allowed to obtain a great number of total nucleated cells and hematopoietic progenitor cells [54,55]. In a clinical trial conducted on 31 patients receiving two different units of UCBsc, one of which expanded ex vivo with MSCs, a significant improvement of early UCBsc engraftment with respect to the infusion of the un-manipulated UCBsc unit only was shown.…”
Section: Clinical Applications Of Mscs In Allo-hsct and Gvhdmentioning
confidence: 99%